Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content1. The Effect of a Proposed Educational Program Using Kinesthetic Storytelling on the Basic Motor Skills Grade One Students in Sultanate of OmanMrs. Alya Masaud Hamdoon Al-Siyabi , Dr. Badria Khalfan Al-Hadabi2. The effect of using multimedia in teaching Arabic Language on developing reading comprehension skills among Primary School Student in Al-Jizah districtMrs. Hala Nawaf Alzaben , Dr. Hamzeh Abdelfattah Alassaf3. The Reality of Using the Blended Learning Strategy in Teaching Chemistry for Secondary School Students from the point of View of Teachers and Educational Supervisors in The Kingdom of Saudi ArabiaMrs. Wardah Gharman Alamri, Co-Prof. Ghadir Zinedine Felemban , Asst-Prof. Fadwa Felemban 4. The Impact of Using Problem-Solving Strategy on Metacognition Thinking and Motivation  towards Learning Mathematics among Fourth Basic Grade Students in JordanMrs. Raidah Hassan Nimr Abdul Rahman, Prof. Odeh Abdel-Gawad Abu Sneineh5. The effect of designing an interactive e-book on learning engagement for sixth graders with learning disabilitiesMrs. Hessah Abdullah Al-Otaibi, Co-Prof. Abdel-Raouf Mohamed Ismail6. Synthesis of Augmented Reality Use in the Development of English Language Writing SkillsMrs. Hadeel Hassan Al-Hazmi, Co-Prof. Mai M. Lutfi Al-Najami7. The Effect of Using Interactive English Language E-Book for the Fourth Graders' Listening  and Reading Skills and Their Reflective Thinking at Martyr Yasseir Arafat Secondary SchoolMr. Mohammad Mahmoud Rjoob
Keywords: Journal of Curriculum and Teaching Methodology